Pengaruh Cyberloafing terhadap Kinerja Karyawan melalui Self Control Sebagai Variabel Moderasi pada PT Swadharma Sarana Informatika Surabaya - Hanum Sulistyowati; Dewi Nuraini (Jurnal Bintang Manajemen, 2025)
The purpose of this study was to determine the test results and analysis of the effect of cyberloafing on employee performance through self-control as a moderating variable at PT Swadharma Sarana Informatika Surabaya. The population and sample in this study were 86 active employees at PT Swadharma Sarana Informatika Surabaya, the sampling used was a census. The analysis method used was SPSS with Moderated Regression Analysis (MRA) analysis for testing hypothesis 3 which is a special application of multiple linear regression. The results showed that cyberloafing had a negative and significant effect on employee performance, self-control had a positive and significant effect on employee performance and self-control weakened the relationship between cyberloafing and employee performance.